Análise do papel dos ácidos graxos de cadeia curta nas infecções causadas por vírus respiratórios - Fernandes, Krist Helen Antunes (2021)
Short-chain fatty acids (SCFAs) are the main metabolites resulting from the fermentation of prebiotics by intestinal bacteria. These exert several physiological functions, including modulation of the immune system, attenuating inflammatory conditions. Respiratory syncytial virus (RSV) and rhinovirus (HRV) are ubiquitous viruses in the environment and prevalent associated with respiratory tract infection, especially in children. There is currently no vaccine available and therapeutic methods to mitigate the severity of the disease caused by these viruses are limited. Natural alternatives, such as the use of prebiotics, soluble dietary fibers, have been studied to prevent respiratory diseases. Based on this, our hypothesis is that short-chain fatty acids may be associated with less severe disease caused by RSV and HRV, modulating the response to viruses. Thus, this work had as main objective to evaluate the effects of SCFAs on the infection caused by the RSV and HRV viruses. In the first study we identified that the diet rich in soluble fibers increases the levels of acetate protecting against infection caused by RSV. The protective effect conferred by acetate was due to the increase in the production of IFN-β in the lungs, and this mechanism depends on the GPR43 and IFNAR receptors. In the second study, we observed that the levels of acetate in the feces of infants with bronchiolitis caused by RSV were directly associated with the improvement of disease severity parameters. Ex vivo treatment with SCFAs of cells obtained from the nasal wash of these patients reduced viral load, and acetate was able to increase the expression of RIG-I, MAVS and ISG15. In the third study, we found that treatment with acetate in human epithelial bronchial cells protects against infection with HRV, reducing the presence of the virus and increasing the gene expression of IFN-β, IFN-λ and viperin. In an experimental model of HRV infection, treatment with acetate increased the expression of IFN-λ, however, after 4 and 6 days of infection and treatment, it reduced the expression of Muc5AC in the lungs. Together, the results of the three studies demonstrate an important role of fatty acids, especially acetate, in infections caused by RSV and HRV, through the modulation of IFN-β and its ISGs and IFN-λ.